Knowledge Understanding and Utilization of Medicinal Plants by Local Community Tompu District of Kaili, Sigi Biromaru, Central Sulawesi - Ifandi, Slamet; Jumari, Jumari; Suedy, Sri Widodo Agung (Biosaintifika: Journal of Biology & Biology Education, 2016)
Kaili is one of the ethnic region in Central Sulawesi which saves a lot of cultural values and traditions. As a traditional community, their life is very dependent upon natural resources contained in the environment. They still have knowledge, traditional culture, treatment and utilization system against various types of plants. The purpose of the study was to examine the knowledge understanding and utilization of medicinal plants by local community Tompu District of Kaili. Data knowledge and utilization were collected through interview, literature study, exploratory survey methods, PEA (participatory ethnobotanical appraisal), questionnaire and from interviews with the informants. The results from interviews showed that of public knowledge is still based on the traditional concept. Based on the results identifications obtained by (90 species). As many as six species medicinal plants to often used the Tompu community are Euphorbia hirta L. Phyllanthus niruri L. Ageratum L. Blumea conyzoides balsaminifera L. (DC). Kleinhovia hospita L and Tabernaemontana pandacaqui. The benefits of this research to the development of science is expected to be complete scientific data regarding the utilization of medicinal plants natural resources on Tribal society Kaili in Tompu.How to CiteIfandi, S., Jumari, J., & Suedy, S. W. A. (2016). Knowledge Understanding and Utilization of Medicinal Plants by Local Community Tompu District of Kaili, Sigi Biromaru, Central Sulawesi. Biosaintifika: Journal of Biology & Biology Education, 8(1), 1-11.